1998
DOI: 10.1046/j.1432-1327.1998.2570169.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of phospholipase C δ3 in the cell and regulation of its activity by phospholipids and calcium

Abstract: The localization of phospholipase C δ3 (PLC δ3) in the cell and its regulatory properties has been investigated. Western blotting showed that human platelet PLC δ3 is located in the membrane and cytosolic fraction. The enzyme amount in the cytosolic fraction was significantly lower than that in the membrane fraction. In rat liver, PLC δ3 was present in both the membrane and cytosolic fraction and was absent in nuclei. Examination of the effects of phospholipids on PLC δ3 revealed that this enzyme is inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 42 publications
0
25
1
Order By: Relevance
“…1) deserves some comment because level of PI-PLC d3, which is poorly expressed in normal tissues [Pawelczyk, 1999] but is highly expressed in C6 astrocytoma cells (Figs. 1B and 3) and other neoplastic tissues [Pawelczyk and Matecki, 1998], may be interpreted as a neoplastic upregulation of this enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) deserves some comment because level of PI-PLC d3, which is poorly expressed in normal tissues [Pawelczyk, 1999] but is highly expressed in C6 astrocytoma cells (Figs. 1B and 3) and other neoplastic tissues [Pawelczyk and Matecki, 1998], may be interpreted as a neoplastic upregulation of this enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PI-PLC d1 is widely expressed in many tissues, but especially in cultured cells [Tanaka and Kondo, 1994;Adamski et al, 1999;Yamaga et al, 1999;Mao et al, 2000;Faenza et al, 2004]. PI-PLC d3 also has been identified in many histotypes at low concentrations [Pawelczyk and Matecki, 1998]; PI-PLC d4 is expressed in the brain as well as in regenerating tissues [Pawelczyk, 1999]; PI-PLC g1 is expressed in keratinocytes and foetal cartilage [Ananthanarayanan et al, 2002] and has been found almost exclusively in the cytoplasm [McBride et al, 1991;Diakonova et al, 1997]; also PI-PLC e occurs in many tissues [Wing et al, 2003]. Notwithstanding the growing interest for the role played by the PI-PLC family enzymes in the nervous system [Ledeen and Wu, 2004], no definitive studies have been accomplished in glial cells [Choi et al, 1989;Tallant and Higson, 1997;Wang and Reiser, 2003].…”
mentioning
confidence: 99%
“…This isoform showed a few notable differences from its sister, PLC␦1, in cellular distribution and sensitivity to lipids and detergents and in the importance of its PH domain in regulation (1202,1203). Recent data indicated that PLC␦3 downregulates RhoA and promotes neurite outgrowth in primary cortical neurons (823).…”
Section: Plc␦3mentioning
confidence: 99%
“…This gene encodes a protein called phospholipase Cδ3, which is located in the cell membrane and is involved in cell membrane signaling. Control of PLCD3 activity is one of the major starting points of cell regulation (21,22). Therefore, its biological function is involved in the control of the cell cycle by means of the activation of protein kinase C, intracellular storage of Ca +2 ions, signal transduction, and transport through the cell membrane.…”
Section: Discussionmentioning
confidence: 99%